MT-CO1 expression in nine organs and tissues of different-aged MRL/lpr mice: Investigation of mitochondrial respiratory chain dysfunction at organ level in systemic lupus erythematosus pathogenesis - Xinglan Huang,; Peng Yan,; Xinghua Song,; Suiying Zhang,; Yuqiong Deng,; Caifeng Huang,; Xiaoqing Zhao,; Sheng Liu,; Xiping Cheng,; Dongjiang Liao, (Archives of Rheumatology, 2022)
Objectives: This study aims to investigate the expression patterns of mitochondrially encoded cytochrome c oxidase 1 (MT-CO1) in different organs and tissues of MRL/lpr mice aged six and 18 weeks. Materials and methods: Six-week-old female MRL/lpr mice (n=10) were considered young lupus model mice, and 18-week-old MRL/lpr mice (n=10) were considered old lupus model mice. Additionally, six-week-old (n=10) and 39-week-old (n=10) female Balb/c mice were used as the young and old controls, respectively. The messenger ribonucleic acid (mRNA) and protein expression levels of MT-CO1 in nine organs/tissues were detected via quantitative polymerase chain reaction (qPCR) and Western blot. Malondialdehyde (MDA) levels were determined with thiobarbituric acid colorimetry. The correlation coefficient of MT-CO1 mRNA levels and MDA levels in each organ/tissue at different ages was analyzed by Pearson correlation analysis. Results: The results showed that most non-immune organs/tissues (heart, lung, liver, kidneys, and intestines) showed increased MT-CO1 expression levels in younger MRL/lpr mice (p<0.05) and decreased MT-CO1 expression in older mice (p<0.05). Expression of MT-CO1 in the lymph nodes was low in younger mice but high in older mice. In other immune organs (spleen and thymus), MT-CO1 expression was low in older MRL/lpr mice. Lower mRNA expression and higher MDA levels were observed in the brains of MRL/lpr mice. However, all MRL/lpr mice showed higher MDA levels than Balb/c mice in every organ no matter younger or older MRL/lpr mice. Conclusion: Our study results suggest that lymphoid mitochondrial hyperfunction at organ level may be an important intrinsic pathogenesis in systemic lupus erythematosus activity, which may affect mitochondrial dysfunction in non-immune organs.